Achieving certainty about the structure of intolerance of uncertainty in a treatment-seeking sample with anxiety and depression - McEvoy, Peter; Mahoney, A. (Pergamon, 2011)
Evidence is accumulating that intolerance of uncertainty (IU) may be a transdiagnostic maintaining factor across the anxiety disorders and depression. However, psychometric studies of the most commonly used measure of IU have typically used undergraduate students, and the factor structure has been highly inconsistent. Previous studies have also tended to focus on one diagnostic subgroup or related symptom, thereby limiting transdiagnostic comparisons. The first aim of this study was to test the latent structure of a commonly used measure of IU in a treatment-seeking sample with anxiety and depression (n = 463). The second aim was to examine psychometric properties of the best fitting solution, including internal reliability, convergent validity, and discriminant validity. Confirmatory factor analysis was used to compare the goodness of fit of five models previously found with undergraduate and community samples. A two-factor solution, comprising of prospective anxiety and inhibitory anxiety, was the best fitting model. The total scale and subscales demonstrated excellent internal reliability. Convergent validity was demonstrated by the scales correlating with symptoms associated with five anxiety disorders and depression, as well as neuroticism, distress and disability. IU explained unique variance in all symptom measures, even after controlling for neuroticism and other symptom measures. Evidence of discriminant validity was also found for each IU subscale. Findings support reliability and validity of the two-factor solution, and are consistent with IU being a transdiagnostic maintaining factor.